Plan de comunicación corporativa para la clínica revelo gray canton Quevedo año 2015 - Parrales Cedeño, Mabel Estefanía (2016)
Through this work the corporate communication plan as part of an organization described because it is an essential tool to project a better image and obtain a consolidated reputation Set best research carried out in the Canton Quevedo, Los Rios Province. In clinical Revelo Gray located on the street fourteenth No. 438 between June Guzman Cortes Avenue and 7th of October. Once the problem of informing research does encountered a corporate communication plan affects the internal and external communication of Revelo Gray Clinic, Quevedo Canton chairs to present as objective, to give them fulfillment strategies are developed to the proper functioning of the plan was also necessary to use research methods known in conjunction with the marketing research types: field in which the primary scene information was obtained, the literature allowed to investigate and review the literature related to the investigation descriptive facilitated awareness of the benefits of research. in this research, an analysis of the organization occurs , the line of business and development achieved by the clinic revealed gray specialties , as well as agencies that control is explained swot matrix explains the development of the internal and external image of the clinic, objectives are set for the development of strategies and actions according to profile customers are also presented, to finalize a projection of a media plan properly with designs of a new corporate image for the clinic revealed a cost of $ 5.980,80ctvs budgeted .